Ação do agonista não-peptídico da angiotensina-(1-7), AVE 0991, nas alterações metabólicas induzidas por suplementação com frutose - Erica Guilhen Mario (2012)
Recent studies have shown that activation of angiotensin-(1-7) / receptor Mas axis plays important role in intermediary metabolism, evidenced by increase in insulin sensitivity. The compound AVE 0991 is a non-peptide angiotensin-1-7 agonist, which effects in intermediary metabolism has not yet been studied. Thus, the objective of this study was to evaluate the action of this agonist on the metabolic changes induced by fructose supplementation. Male Sprague-Dawley rats at 5 weeks of age were utilized. The animals were divided randomically into four groups: Group C: animals fed a commercial diet (control) plus vehicle; Group CA: animals fed a commercial diet treated plus AVE 0991 (gavage at 1mg/kg concentration), Group F: animals fed a commercial diet supplemented with 10% fructose in the drinking water treated plus vehicle; Group FA: animals fed a commer cial diet supplemented with 10% fructose in the drinking water treated plus AVE 0991 (gavage at 1mg/kg concentration). Fructose supplementation promoted glucose intolerance and treatment with AVE 0991 reversed this parameter, besides increasing the hepatic glycogen content and reduces serum levels of insulin, triacylglycerols and non-esterified fatty acids. In addition, in the fructose group, total lipids and triacylglycerols secretion by liver were increased and AVE0991 treatment decreased these parameters . In muscle and adipose tissue, the treatment increased the activity of lipoprotein lipase (LPL), and the expression of genes involved in lipid oxidation such as PPAR and CPT-1 were increased. In adipose tissue, the PPAR gene expression, involved in fat deposition and improvement of insulin sensitivity showed no increase in adipose tissue mass. These results suggest that activation of Mas receptor by AVE 0991 agonist seems to be involved in the improvement of deleterious changes promoted by fructose supplementation.